Narrative Review of Factors Affecting Lower Back Pain among Workers in Pakistan - Arooj, Ayesha; Aziz, Aamir; Khalid, Fariha; Iqbal, M. Hussain (BioScientific Review, 2022)
According to the world health organization (WHO), lower back pain (LBP) is the most common health hazard among workers and is among the top ten health hazards around the globe. The Global Burden of Disease (GBD) 2010 stated LBP as amongst the top 6 diseases which cause disability injuries and other chronic diseases. This is the impairment that poses the most economic burden on society as a whole, including individuals, businesses, and the government. This study aims to find out the factors that affect lower back pain among workers associated with different professions in Pakistan. Data were collected from different databases, such as PubMed, Google scholar, and PEDro by using a predefined search strategy with proper Boolean terms ‘AND’ or ‘OR’ or ‘NOT’. The data were collected from the literature available for past 10 years. Additionally, articles with relevant material and titles were reviewed for conducting the current research review. The most common risk factors that were seen almost among all professions were static position and prolonged working hours, any work that demands prolonged standing or sitting, bending or twisting, and improper lifting. Several professional workers are at high risk for developing LBP but among all the professions physiotherapists, sonographers, bankers, and shopkeepers were at higher verge for developing LBP. It was found that the prevalence of LBP is increasing day by day and significantly affecting workers in every profession. Therefore, timely trainings with proper ergonomic techniques could decrease LBP and increase economic productivity in Pakistan. It can be said that good ergonomics for good economics.